Karakteristik dan Respons Estrus Domba Setelah Pemberian Progesteron-Controlled Internal Drug Release Selama 12 dan 13 Hari (CHARACTERISTIC AND ESTRUS RESPONSE OF EWE TREATED WITH PROGESTERONE-CIDR 12 AND 13 DAYS INTERVAL) - Yasa, Neta Fitria; Karja, Ni Wayan Kurniani; Setiadi, Mohamad Agus (Jurnal Veteriner, 2019)
CIDR is a device to stimulate and controled estrous cycle in livestock. This study aim to investigate the estrus characteristics and responses of ewes CIDR treated for 12 and 13 days interval. CIDR were treated into 16 ewes for 12 days or 13 days interval. The evaluation of clinical sign of estrus, ferning image, vaginal smear sample, and measurement of vaginal mucus resistance with estrus detector, were performed before treatment of CIDR, at 0, 12, 24, 36, 48, and 54 hour after CIDR removal. Ferning image for both group started from 24 hour after CIDR removal with few ferning pattern. 36 hour after CIDR removal, ferning image already clear. 48 hour after CIDR removal, ferning showed the optimum image, and cover all view. 54 hour after removal, ferning started to decrease. The composition of vaginal epithel dominated by superficial cell started at 24 hours after CIDR removal followed by appearance of estrus sign. The mean of estrus mucus resistance in both groups showed high values before estrus then decreased during estrus. The means of electrical resistance value for both group approximately 310Ù to 700Ù before estrus and approximately 210Ù to 290Ù during estrus. The number of ewes shown the sign of estrus were 75% in group of 12 days interval and 100% in group 13 days. The mean of onset estrus for 12 and 13 days interval groups are 28 and 30 hours after CIDR removal respectively. In conclution, the results of this study showed that CIDR treatment for 13 days show better intensity of estrus sign than 12 days interval group.